Development Of Conventional Real-Time And Thermostabilised Multiplex PCR For The Detection Of Toxoplasma Gondii - Rahumatullah, Anizah (2012)
Toxoplasma gondii is an important pathogen in veterinary and human medicines. It is widely distributed throughout the world and has a broad range of hosts that includes warm-blooded animals as intermediate hosts and felid (cat) as the definitive host. Infection with this parasite is usually asymptomatic in healthy individuals but can cause morbidity and mortality in immunocompromised patients and in congenitally infected infants. Molecular biology is increasingly being used as a diagnostic method for diagnosis of toxoplasmosis, especially for specimens collected from amniotic fluid, cerebrospinal fluid, placenta tissue, blood and eye fluid. However, the existing PCRbased methods for the detection of Toxoplasma DNA suffer from variations in performance among the laboratories. Indeed, the use of PCR-based assay for diagnosis of Toxoplasma is still uncommon in Malaysia. The aim of this study is to develop rapid, specific and sensitive PCR-based assays to detect T. gondii DNA for diagnosis of toxoplasmosis. Three PCR-based assays namely conventional multiplex PCR, realtime multiplex PCR and thermostabilised PCR for the detection of T. gondii DNA were developed. All the primers and probes used were newly designed and optimized. All three PCR assays showed 100% specificity whereby no cross-reactivity with other organisms was observed.